Clinico-Pathological Profile of Relapsed Multiple Myeloma in Low-Resource Setting: A Single-Center Study from Nepal - Jha, Ajaya Kumar; Shrestha, Prakash; Subedi, Garima (Nepalese Journal of Cancer, 2026)
Introduction: Multiple myeloma is a plasma cell malignancy with improved survival in the modern era; however, relapse remains inevitable in most patients. Data on relapsed multiple myeloma from Nepal are limited. Objective: To study the clinico-pathological profile, treatment patterns, and outcomes of relapsed multiple myeloma. Methods: A descriptive case series study was conducted at a tertiary care center in Nepal from January 2023 to August 2025. Patients with relapsed multiple myeloma were analyzed for clinical, laboratory, radiological, and treatment-related parameters. Results: Twelve patients were included in the study. Mean age of presentation was 61.8 years (range: 44 – 74 years) with a male predominance (75%). Bone pain was the most common symptom (83%). Raised beta-2 microglobulin was seen in 78%, and lytic bone lesions in 75%. IgG kappa was the predominant subtype (67%). PET-CT and cytogenetics was done in 17%. All patients received bortezomib-based therapy initially, however Carfilzomib based triplet regimen was restricted to 17% only after relapse. Total duration of follow up since first diagnosis was 110 months and survival at last follow-up was 83%. Conclusion: Relapsed multiple myeloma poses significant challenges in resource-limited settings due to restricted diagnostic and therapeutic options.